Nitrogen Recovery Efficiency from Urea Treated with NSN Co-Polymer Applied to No-Till Corn - Barbieri, Pablo; Sainz Rozas, Hernan Rene; Echeverria, Hernan Eduardo (MDPI, 2020)
Nitrogen (N) rate increases used by many farmers produce a reduced or null effect on N recovery efficiency (RE) by crops. Therefore, management practices to reduce N losses and increase RE are necessary. Co-polymer maleic itaconic acid (NSN) have become available for use with urea and has shown potential in reducing N losses. The objective of this study was to evaluate the effectiveness of urea treated with NSN on grain yield and RE in a no-till corn. A field experiment was carried out at Balcarce, Argentina over three years, evaluated treatments were urea and urea + NSN at 120 N kg ha−1, and additional 0 N treatment was included. Urea + NSN was effective to reduce total ammonia volatilization losses, and the average of two years were 1.4 (1.1% to N applied) and 8.7 kg ha−1 (7.2% to N applied) for urea + NSN and urea, respectively. However, while grain yield and N grain removal were not affected by urea + NSN, the N rate significantly increased grain yield and N grain removal. Nitrogen recovery efficiency was not affected by urea + NSN, RE (average of three years) was 29.0% and 27.8% for urea and urea + NSN, respectively. In conclusion, there was no advantage of using urea treated with NSN in no-till corn overgrain yield, N grain removal, or RE.